(untitled) (Research, Society and Development, 2020)
Introduction: The infection caused by the new Coranavirus shows great relevance worldwide. Evidence emerged of the need for greater understanding of the relationship between the current pandemic, the biopsychosocial health of nurses and the quality of care. Objective: To identify the conditions imposed by the pandemic on the professional, focusing on perceiving the interference in care for the suspected or confirmed user for COVID-19. Methodology: This is an Integrative Literature Review. In order to compose the search, the Virtual Health Library was used. After applying the selection criteria, five articles were selected to design the study. Results: Sufficient data emerged that point to the high flow of care faced by nurses, the need for greater technical and scientific knowledge and practice or the generation of new skills, as well as the risk of contamination, transmission to themselves and family members, generating consequences on the dynamics of care. Final considerations: Current conditions directly influence professional health and quality of care. Planning is necessary for the frontline professional to maintain his biopsychosocial health in order to preserve assistance based on the principles of humanization.